Low Specific Phosphorus Uptake Affinity of Epilithon in Three Oligo- to Mesotrophic Post-mining Lakes - Konopáčová, Eliška; Nedoma, Jiří; Čapková, Kateřina; Čapek, Petr; Znachor, Petr; Pouzar, Miloslav; Říha, Milan; Řeháková, Klára (Frontiers in microbiology, 2021)
Epilithon contributes to phosphorus (P) cycling in lakes, but its P uptake traits have been rarely studied. We measured the chemical composition of epilithon and its inorganic P uptake kinetics using isotope 33P in three deep oligo- to mesotrophic post-mining lakes in April, July, and October 2019. Over the sampling period, epilithon biomass doubled, while the P content in biomass dropped to 60% of the April values, and the seasonal changes in P content expressed per epilithon area were only marginal and statistically not significant. High epilithic C:P molar ratios (677 on average) suggested strong P deficiency in all investigated lakes. Regarding the kinetic parameters of phosphorus uptake, maximum uptake velocity (V max , seasonal range 1.9-129 mg P g OM-1 h-1) decreased by an order of magnitude from April to October, while half-saturation constant (K S , seasonal range 3.9-135 mg P L-1) did not show any consistent temporal trend. Values of epilithic specific P uptake affinity (SPUA E , seasonal range 0.08-3.1 L g OM-1 h-1) decreased from spring to autumn and were two to four orders of magnitude lower than the corresponding values for seston (SPUA sest ), which showed an opposite trend. Considering our results, we suggest a possible mechanism underlying a stable coexistence of planktonic and epilithic microorganisms, with plankton prospering mostly in summer and autumn and epilithon in winter and spring season. Additionally, a phenomenon of reversible abiotic P adsorption on epilithon was observed.
Keywords: epilithon; hydric recultivation; periphyton; oligotrophic lakes; specific P affinity; phosphorus uptake